2020
DOI: 10.5902/1980509824460
|View full text |Cite
|
Sign up to set email alerts
|

Fair value of standing timber in the context of IAS 41 implementation: a case study with <i>Pinus radiata</i>

Abstract: Upon seeing the forest valuation in a knowledge-based framework and, although there are studies that indicate how the Chilean forestry companies evaluate their forestry assets, existing information can be inferred only on large and medium-sized enterprises; in the case of small enterprises there are no tangible data to know what the method of valuation of its assets. To provide a critical assessment of the valuation methods commonly used for the valuation of forests, this paper has two objectives. First, to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
1
1
0
3
Order By: Relevance
“…The use of discounted cash flow prevailed in companies that operate with biological assets, especially those that require level 3 information at the value hierarchy. This is confirmed by previous studies that found the choice of discounted cash flow for most agribusiness companies , or which proposed calculation methodologies using the technique (Acuña et al, 2020;R. L. M. Silva et al, 2022).…”
Section: Figure 3 Forest Measuring Techniquesupporting
confidence: 83%
See 1 more Smart Citation
“…The use of discounted cash flow prevailed in companies that operate with biological assets, especially those that require level 3 information at the value hierarchy. This is confirmed by previous studies that found the choice of discounted cash flow for most agribusiness companies , or which proposed calculation methodologies using the technique (Acuña et al, 2020;R. L. M. Silva et al, 2022).…”
Section: Figure 3 Forest Measuring Techniquesupporting
confidence: 83%
“…This study focused on the forest segment (pulp and paper, wood, and other products with forest assets), aiming to advance knowledge on accounting choices in the recognition and measurement of biological assets under IFRS -considering that forest assets are among the most complex for valuation and disclosure (Acuña et al, 2020;Machado et al, 2014), in addition to questions regarding the relevance of measuring these assets at fair value, based on IAS 41 (Pereira et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…O maior número de escolhas (ou as mais subjetivas) ocorre nos segmentos com ativos sem mercado ativo, cuja estimativa de valor justo está no nível 3 da hierarquia (IFRS 13 -mensuração a valor justo, aplicada a partir do ano de 2013), que exigem técnica específica de avaliação -como é o caso de florestas e cana de açúcar em pé (Acuña et al, 2020;. Nesses casos, as escolhas se concentram na definição de premissas da avaliação, com base em dados internos gerados por gestores, a exemplo do montante de fluxos futuros de caixa (receitas menos despesas) em cada um dos anos da vida útil do ativo, da taxa de desconto, do índice de crescimento do ativo, dentre outras (L. He, 2020;Lento et al, 2018;Pereira et al, 2020).…”
Section: Escolhas Contábeis E Comparabilidade Da Informaçãounclassified
“…A escolha de entidades que atuam com florestas é justificada por três aspectos: i) representatividade econômica da indústria (papel/celulose, madeira) (IBA, 2019); ii) o alto grau de discricionariedade/subjetividade na mensuração, disclosure e apresentação de relatórios desses ativos biológicos (Machado et al, 2014;Pereira et al, 2020), dadas as suas particularidades, como o longo ciclo produtivo e a falta de mercado ativo para a mensuração da floresta em crescimento (Acuña et al, 2020;Ortiz & Oliveira, 2020); e iii) a ausência de consenso sobre os principais elementos da contabilização de florestas ao longo dos países, como os critérios de mensuração, procedimentos de divulgação e forma de apresentação nas demonstrações (Bohušová et al, 2012;Budrionyte & Gaizauskas, 2018;Giertliova et al, 2017;Herbohn & Herbohn, 2006;Stárová et al, 2016).…”
Section: Introductionunclassified
“…Dentre a gama de ativos biológicos existentes, optou-se por estudar a cana-deaçúcar em função de alguns aspectos. Primeiramente, poucos estudos se concentram em discussão sobre ativos biológicos resultantes de bearer plants (Silva, Nardi, Mendes, & Oliveira, 2022;Acuña, Pinto, Cancino, & Sandova, 2020;Cavalheiro, Gimenes, Binotto & Fietz, 2019;Machado, Martins, & Carvalho, 2014). Em segundo lugar, a cana-deaçúcar foi considerada a colheita primária mais produzida do mundo em 2019, representando 21% da produção mundial de culturas, sendo a principal commodity encontrada (FAO, 2021), sendo importante para países como: Brasil, Paquistão, México, Colômbia e Austrália (FAOSTAT, 2020), os quais adotam as IFRS -International Financial Reporting Standards.…”
Section: Introductionunclassified